SISTEM KOMUNIKASI KELOMPOK - Nurhanifah Nurhanifah; Muhammad Yasir Halomoan Nasution; Ardiansyah Ardiansyah (JGK (Jurnal Guru Kita), 2022)
The purpose of this study is to discuss the communication system in groups, the research method is a research library, the results of this study are: 1. Group Communication is communication that takes place between a communicator and a group of people who number more than two people who have the same goal and interact with each other to achieve these goals. Communication that takes place in a group or group about issues that concern the interests of many people in the group. So group communication appears to be more open when compared to individual communication. 2. Community development is an approach in improving people's lives through giving power to community groups to be able to create, use and control the resources that exist in their environment. As a social work method, community development refers to the active interaction between social workers and the community with which they are involved in the process of planning, implementing, monitoring and evaluating a social welfare development program. 3. The Qur'an does not specifically describe group communication, but there are many verses that provide an overview of the group communication process. Some words in the Qur'an are assumed to be an explanation of the form of group communication. In the Islamic perspective, group communication occurs because humans cannot be separated from interactions with others. Therefore, it can be said that Islam is a communication-based religion. God created humans with the basic function of communicating. Furthermore, the communication system of Islamic groups is built based on the Qur'an, because the Qur'an contains the magic of the group communication process, both from the language used and the method of communication.